Modulation of tissue tropism and biological activity of exosomes and other extracellular vesicles: New nanotools for cancer treatment. (September 2016) - Kooijmans, Sander A.A.; Schiffelers, Raymond M.; Zarovni, Natasa; Vago, Riccardo
Graphical abstract: Abstract: Exosomes are naturally secreted nanovesicles that have recently aroused a great interest in the scientific and clinical community for their roles in intercellular communication in almost all physiological and pathological processes. These 30⿿100 nm sized vesicles are released from the cells into the extracellular space and ultimately into biofluids in a tightly regulated way. Their molecular composition reflects their cells of origin, may confer specific cell or tissue tropism and underlines their biological activity. Exosomes and other extracellular vesicles (EVs) carry specific sets of proteins, nucleic acids (DNA, mRNA and regulatory RNAs), lipids and metabolites that represent an appealing source of novel noninvasive markers through biofluid biopsies. Exosome-shuttled molecules maintain their biological activity and are capable of modulating and reprogramming recipient cells. This multi-faceted nature of exosomes hold great promise for improving cancer treatment featuring them as novel diagnostic sensors as well as therapeutic effectors and drug delivery vectors. Natural biological activity including the therapeutic payload and targeting behavior of EVs can be tuned via genetic and chemical engineering. In this review we describe the properties that EVs share with conventional synthetic nanoparticles, including size, liposome-like membrane bilayer with customizable surface, and multifunctional capacity. We also highlight unique characteristics of EVs, which possibly allow them to circumvent some limitations of synthetic nanoparticle systems and facilitate clinical translation. The latter are in particular correlated with their innate stability, ability to cross biological barriers, efficiently deliver bioactive cargos or evade immune recognition. Furthermore, we discuss the potential roles for EVs in diagnostics and theranostics, and highlight the challenges that still need to be overcome before EVs can be applied to routine clinical practice.